The Influence and Mechanism of Chinese Martial Arts on Improving Interpersonal Skills in Adolescents: A Randomized Controlled Trial - Dou dou Yang; Qiong Yao; Xiao yan Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Unlike other forms of martial arts, Chinese Wushu can fortify both the physical and mental health of adolescents. However, limited research has been conducted on the social benefits derived from Chinese martial arts. Grounded in the principles of embodied cognition theory, this study employs the technique of a randomized controlled trial to establish a causal link between Chinese martial arts and the development of interpersonal skills in adolescents. It further explores the mediating role of psychological quality and the potential moderating influence of an only-child status. The practice of Chinese martial arts exhibits a substantial positive impact on interpersonal skills (β=0.161, p < 0.01). Additionally, psychological wellbeing fully mediates the relationship between Chinese martial arts and interpersonal skills (β=0.017, 95% CI= [-0.098, 0.146]). Intriguingly, the mediating role of psychological wellbeing is moderated by the factor of only-child status (β=0.216, 95% CI= [0.050, 0.390]). Embodied cognition theory posits that the integration of internal psychological processes with external bodily dynamics leads to a state of harmony and unity. Training in Chinese martial arts enhances psychological well-being through the interaction between the body and its environment. Furthermore, due to the compensation effect and peer influence, Chinese martial arts as a teamwork are particularly advantageous for only children. Training in Chinese martial arts enhances psychological quality by harmonizing internal psychological processes with external bodily dynamics. Furthermore, due to the compensation effect and peer influence, practicing Chinese martial arts as a group activity proves particularly advantageous for only children. The conclusion of this study integrates the principles of Chinese martial arts with embodied cognition theory, providing both a theoretical framework and practical insights. These findings are intended to inform and guide policy formulation regarding Chinese martial arts education by the relevant authorities.